In-Water Synthesis of Quinazolinones from 1,1-Dichloro-2-nitroethene and Anthranilamides - Zhu, Fengjuan; Song, Runjiang; Li, Shen; Shao, Xusheng (Synlett, 2016)
An efficient synthetic methodology was developed for direct formation of quinazolinones with 2-nitromethyl substituent via 1,1-dichloro-2-nitroethene and anthranilamides. This strategy provides an alternative for quinazolinones construction with merits of proceeding in water, easy purification, and no addition of catalysts.
Keywords: synthetic methodology; quinazolinones; 2-nitromethyl; 1,1-dichloro-2-nitroethene; anthranilamides